Ibn Khaldun and Music as a Science of Mathematical Sciences - Çetinkaya, Yalçın (İbn Haldun Çalışmaları Dergisi, 2017)
In his book Mukaddima, Ibn Haldun (1332-1406) considers music as a science amongst the other rational (philosophical) sciences. According to Ibn Haldun, there are seven rational (philosophical) sciences and logic (Mantık) is first amongst them. Then follow the sciences of arithmetic, geometry, cosmography of mathematical sciences and music, natural sciences and theology. Ibn Haldun recognizes the science of music as one which determines the correlation of sounds to tunes in terms of numbers and investigates measurement methods. Its benefit is to teach the necessary range of singing tunes. Ibn Haldun is a significant Muslim scholar who studied music from all aspects. In Ibn Haldun’s 14th and 15th century work on music theory, one can access to important philosophical and practical information about music. The fact that he includes music under the categories of wisdom and philosophy is indicative of the position of music among early Muslim thinkers.